Anesthesia for Panendoscopy : The Challenging Role of Nurse Anesthetist - Junyatham, Sirijunya; Hengphaisan, Saranya; Mettapol, Chanisa; Chumpathong, Saowapark (Journal of The Royal Thai Army Nurses, 2023)
Panendoscopy is a diagnostic procedure in uncertain malignancy patients according to head and neck lesions. Steps by steps direct visualization and tissue biopsy would be performed to identify the origin and stage of malignancy. Anesthetic management of the procedure can be challenging due to stenotic airway, concurrent airway sharing among surgeons and anesthesiologists. Airway management, detection, and treatment of intraoperative airway obstruction and desaturation are crucial. An expert nurse anesthetist is essential for patient care. The role of a nurse anesthetist is highly demanding, physically evaluated and mentally prepared during the preoperative visit, room set up with medication and specialized equipment, cooperating with the anesthesiologist during the procedure and handing over the patient to the postanesthetic care unit, and early detection of any postoperative complications, aiming for the best perioperative outcome for the patients.